Effects of ribavirin on respiratory syncytial virus in vitro. - Hruska, J F (1980)
Ribavirin was demonstrated to have an antiviral effect on respiratory syncytial virus in vitro. A 50% reduction in plaque number was observed at concentrations of 3 or 10 micrograms of ribavirin per ml. This effect was observed when the drug was added as late as 12 h postinfection. At concentrations of greater than 10 micrograms of ribavirin per ml, the size of the syncytial plaque also noticeably decreased. Ribavirin similarly decreased the number of infectious units released into the culture supernatant. The antiviral effect was observed to be inversely related to the size of the viral inoculum, although all concentrations above 3.2 micrograms of ribavirin per ml visibly lessened the cytopathic effect regardless of the inoculum. Cloning of respiratory synctial virus in inhibitory concentrations of ribavirin failed to show increased resistance to the drug.